2015
DOI: 10.1017/s0022215115001346
|View full text |Cite
|
Sign up to set email alerts
|

Face and content validation of a novel three-dimensional printed temporal bone for surgical skills development

Abstract: A sophisticated three-dimensional printed temporal bone that demonstrates face and content validity was developed. The efficiency in cost savings coupled with low associated biohazards make it likely that the printed temporal bone will be incorporated into traditional temporal bone skills development programmes in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 12 publications
1
53
0
12
Order By: Relevance
“…3D-printed models have been used to perform common navigation maneuvers and presurgical planning in various subspecialties, opening new avenues for their use as surgical training tools. 3D-printed models have already been shown to be effective for training in temporal bone simulation 44,45 as well as in training of microtia 46 and endoscopic endonasal surgery. 10,47 Recently, Al-Ramahi and colleagues 48 developed a 3D-printed airway model for rigid bronchoscopy foreign body removal training.…”
Section: Examples Of 3d Printing Clinical Applications In Oto-hnsmentioning
confidence: 99%
“…3D-printed models have been used to perform common navigation maneuvers and presurgical planning in various subspecialties, opening new avenues for their use as surgical training tools. 3D-printed models have already been shown to be effective for training in temporal bone simulation 44,45 as well as in training of microtia 46 and endoscopic endonasal surgery. 10,47 Recently, Al-Ramahi and colleagues 48 developed a 3D-printed airway model for rigid bronchoscopy foreign body removal training.…”
Section: Examples Of 3d Printing Clinical Applications In Oto-hnsmentioning
confidence: 99%
“…However, due to limitations of cadaveric material, synthetic temporal bones have been developed for training such as the Pettigrew temporal bone with variable success [33]. There have been other non-virtual reality models that have been developed for temporal bone drilling, with different forms of validation [34][35][36][37][38].…”
Section: Otology Simulatorsmentioning
confidence: 99%
“…The use of 3D-printed models, however, potentially reduces reliance on the acquisition of cadaveric bone. Research has shown that these models are an acceptable alternative [29][30][31] .…”
Section: Limitationsmentioning
confidence: 99%
“…This technology enables physician learners to practice these skills while lessening the danger to patients through the use of complex high fidelity models 29 . For example, multiple centers have reported data on 3D-printed temporal bones in the education of their trainees [29][30][31] . During implementation, participants were asked to qualitatively evaluate these training exercises in terms of realism, anatomical accuracy, utility, and efficacy.…”
mentioning
confidence: 99%